2018
DOI: 10.1525/collabra.100
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Evidence for Context-Sensitive Derivation of Scalar Inferences

Abstract: A scalar expression like some can optionally have an enriched interpretation (approximately meaning "some, but not all") depending on the context in which it appears. Numerous experiments using the self-paced reading method have found evidence that context has an online effect on the interpretation of a scalar term, resulting in faster or slower reading times for a later phrase whose comprehension is dependent on the interpretation of some. The present study used eye movements to isolate the time course of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Overall, we found that native speakers as a group do distinguish the meaning of some based on the QUD, such that the not all implicature is more likely to arise under an upper-bound QUD than a lower-bound QUD. While the interpretation of some is typically described as context-sensitive in linguistic analyses, the findings of the current study converge with those of a still relatively limited number of experimental studies in demonstrating sensitivity to QUD in the interpretation of some during language comprehension ( Politzer-Ahles and Fiorentino, 2013 ; Degen and Goodman, 2014 ; Dupuy et al, 2016 ; Politzer-Ahles and Husband, 2018 ). However, the findings of the current study also revealed individual differences in the extent to which QUD affects the interpretation of some , which depended both on an individual’s cognitive resources and on their personality-based pragmatic abilities.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Overall, we found that native speakers as a group do distinguish the meaning of some based on the QUD, such that the not all implicature is more likely to arise under an upper-bound QUD than a lower-bound QUD. While the interpretation of some is typically described as context-sensitive in linguistic analyses, the findings of the current study converge with those of a still relatively limited number of experimental studies in demonstrating sensitivity to QUD in the interpretation of some during language comprehension ( Politzer-Ahles and Fiorentino, 2013 ; Degen and Goodman, 2014 ; Dupuy et al, 2016 ; Politzer-Ahles and Husband, 2018 ). However, the findings of the current study also revealed individual differences in the extent to which QUD affects the interpretation of some , which depended both on an individual’s cognitive resources and on their personality-based pragmatic abilities.…”
Section: Discussionsupporting
confidence: 82%
“…More broadly, it may also be interesting for future research to examine to what extent language skills as well as cognitive resources and personality-based factors may influence the derivation of implicatures for scalar terms other than the quantifier some . Moreover, future research examining individual differences in sensitivity to context in the interpretation of scalar terms using online measures such as self-paced reading (e.g., Breheny et al, 2006 ; Politzer-Ahles and Fiorentino, 2013 ), eye-tracking (e.g., Politzer-Ahles and Husband, 2018 ), or neurolinguistic methods (e.g., Hartshorne et al, 2015 ; Politzer-Ahles and Gwilliams, 2015 ), may also provide new insights regarding how individual differences in the domains examined in the current study impact the derivation of scalar implicatures during the dynamics of language processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Converging evidence for the incremental use of scalar inferences to update processing predictions comes from Hartshorne, Azar, Snedeker, and Kim (2014), who adapted a paradigm widely used in reading time research (Bergen & Grodner, 2012; Breheny et al, 2006; Hartshorne & Snedeker, 2014; Politzer‐Ahles & Fiorentino, 2013; Politzer‐Ahles & Husband, 2018) to show that the derivation of scalar implicatures is sensitive to context. In this paradigm, people read a sentence in which some is embedded in a context that either does or does not support scalar implicatures, and then a later word in the sentence serves as a probe for whether the inference was realised.…”
Section: What Previous Event‐related Potential Studies Have Shownmentioning
confidence: 99%
“…Scalar implicature has long been one of the most studied phenomena in experimental pragmatics—indeed, the study of scalar implicature played a seminal role in the emergence of ‘experimental pragmatics’ as a field. Much research on the computation of scalar implicatures relies on behavioural measures, including explicit judgements about the meanings of various utterances under various conditions (Bott & Noveck, 2004; Bott, Bailey, & Grodner, 2012; Chemla & Spector, 2011; Chevallier et al, 2008; De Neys & Schaeken, 2007; Degen, 2015; Dieussaert, Verkerk, Gillard, & Schaeken, 2011; Doran, Baker, McNabb, Larson, & Ward, 2009; Feeney, Scafton, Duckworth, & Handley, 2004; Geurts & Pouscoulous, 2009; Goodman & Stuhlmüller, 2013; Marty & Chemla, 2013; Marty, Chemla, & Spector, 2013; van Tiel, van Miltenburg, Zevakhina, & Geurts, 2016; among others), reaction and reading time measures (Bergen & Grodner, 2012; Bezuidenhout & Cutting, 2002; Bott & Noveck, 2004; Breheny, Katsos, & Williams, 2006; Chemla, Cummins, & Singh, 2017; Hartshorne & Snedeker, 2014; Noveck & Posada, 2003; Politzer‐Ahles & Fiorentino, 2013; Politzer‐Ahles & Husband, 2018; among others), measures of eye movements (Breheny, Ferguson, & Katsos, 2012, 2013; Degen & Tanenhaus, 2015; Grodner, Klein, Carbary, & Tanenhaus, 2010; Huang & Snedeker, 2009; among others) and mouse tracking (Tomlinson, Bailey, & Bott, 2013). Recent reviews of these literatures are available in, for example, Chemla and Singh (2014a,b) and Sauerland and Schumacher (2016).…”
Section: Introductionmentioning
confidence: 99%